Optimization of bacterial cellulose production in apple juice medium by using response surface methodology (RSM) - Abu Hassan, Mohd Nazir (2012)
Acetobacter xylinum is a type of acetic acid producing bacteria that can synthesis bacterial cellulose from carbohydrates.Bacterial cellulose that produced has high purity,high water holding capacity,good mechanical strength,elasticity,high crystallinity and high porosity compare to plant cellulose.This research was using apple juice as the high potential carbon sources to replace the pure carbon sources as the substrate for the synthesis of bacterial cellulose.The objective of this study was to optimize bacterial cellulose production in apple juice medium by using Response Surface Methodology (RSM).The research will be conducted by using 5 samples with difference temperature (28ºC, 29ºC, 30ºC, 31ºC and 32ºC) , 5 sample with difference in pH (4, 5, 6 ,7 and 8) and 5 sample with different medium concentration (60 %, 70%, 80%,90% and 100%).Each sample contains 100mL of medium in 250mL conical flask and incubated in incubator for 5 days.The bacterial cellulose film produced by Acetobacter Xylinum was treated with 1% Natrium Hydroxide (NaOH) for 1 day and then washed with Deionized water to neutralize the bacterial cellulose. The result showed that the medium concentration,pH and temperature of cultivation were affected the production yield of bacterial cellulose.By using response surface methodology (RSM),the optimum condition for bacterial cellulose production was 95% (v/v) for medium concentration, pH 5.95 and cultivation temperature at 30.3ºC.The film then was analyzed by using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). By using FTIR the hydrogen bonds (-OH) of bacterial cellulose was determined while by using SEM the interwoven strands,ribbon-like (microfibrils) of bacterial cellulose structure was observed.Thus,the optimum conditions for bacterial cellulose production can be determined by using RSM.